Three judgments to end the debate on the legality of the Covid vaccine. Italian Constitutional Court, Judgements 14, 15, 16 of 2023 and the problematic practice of anticipating the content of judgements in the Court's press releases (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The Italian Constitutional Court's rulings 14, 15 and 16 of 2023 unified numerous appeals, filed by the ordinary and administrative Courts, concerning legislative interventions aimed at imposing compulsory vaccination against covid-19 on specific categories of workers. The article examines the three rulings jointly, highlighting how the court took a clear stand against anti-scientific positions on the safety and effectiveness of vaccination and did not find any illegitimacy profiles with regard to the labour law consequences for non-vaccinated workers. Lastly, some critical remarks are made concerning the large period of time that elapsed between the issuing of the press release and the actual publication of the judgments.
Keywords: Constitutional Court; Constitutional Justice; Vaccination; Covid-19; Constitutional Court’s Press Release